2022
DOI: 10.3390/ijerph19063188
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How and Why Alcohol Interventions Prevent and Reduce Problematic Alcohol Consumption among Older Adults: A Systematic Review

Abstract: Problematic alcohol use has been increasing in older adults (55+) in recent decades. Many of the effective interventions that are available to prevent or reduce the negative effects of alcohol consumption are aimed at adults in general. It is unclear whether these interventions also work for older adults. The objective of this review was to understand how (i.e., which elements), in which context, and why (which mechanisms) interventions are successful in preventing or reducing (problematic) alcohol consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 108 publications
(184 reference statements)
1
4
0
4
Order By: Relevance
“…The results showed that most older adults reduce their time engaging in social opportunities in shopping malls after retirement (Taiwanese drinking culture is also regarded as a kind of social interaction), and focus more on the impact of physical health and chronic diseases. The gradual reduction in alcohol intake was consistent with many studies [88][89][90][91]. The current living status of older adults was mostly "living with spouse", followed by "living with spouse or children".…”
Section: Discussionsupporting
confidence: 88%
“…The results showed that most older adults reduce their time engaging in social opportunities in shopping malls after retirement (Taiwanese drinking culture is also regarded as a kind of social interaction), and focus more on the impact of physical health and chronic diseases. The gradual reduction in alcohol intake was consistent with many studies [88][89][90][91]. The current living status of older adults was mostly "living with spouse", followed by "living with spouse or children".…”
Section: Discussionsupporting
confidence: 88%
“…Uitvoerders en initiators van de geïncludeerde programma's (respondenten) werden uitgenodigd om deel te nemen en om hun gedocumenteerde protocollen op te sturen. Deze documenten werden iteratief, oftewel herhaaldelijk, vergeleken en geanalyseerd op basis van de inzichten uit de literatuur over deze programma's, zoals beschreven in de inleiding [12,13], en met inzichten uit literatuuroverzichten over ouderen en problematisch alcoholgebruik [14,15]. Alle inzichten werden samengevoegd en gebruikt om een topiclijst te ontwikkelen (zie digitaal aanvullende content Bijlage -topiclijst).…”
Section: Methodeunclassified
“…De verschillen tussen de onderzoekers werden besproken, en waar nodig werden wijzigingen aangebracht (RR, RB, DvdM). Na deze analysefase werden de categorieën vergeleken met de inzichten uit literatuuronderzoeken naar evidencebased elementen van groepsinterventies gericht op het verminderen van problematisch alcoholgebruik bij ouderen [14,15].…”
Section: Methodeunclassified
See 2 more Smart Citations